The Influence of Principal Leadership, PE Teacher Professional Competence and Teacher Workload toward Sports Achievement in Dieng - Sugiharti, Tanti; Ruslaini, R.; Kasih, Ekawahyu (JURNAL MANAJEMEN BISNIS, 2021)
This research aims to know the influence of the Principal Leadership, PE Teacher Professional Competence, and Teacher Workload on sports achievement at elementary school. The study population is 31 PE (PJOK) teachers from 50 elementary schools in the Dieng plateau, which belong to the District of Kejajar, Wonosobo, and District of Batur, Banjarnegara, Central Java. The survey method is conducted to collect research data and used a quantitative approach to test the hypothesis. The results show that the principal leadership and PE teacher professional competence have no influence on sports achievement at elementary school. Meanwhile, the PE teacher workload, planning, guidance, and student assessment carried out by teachers significantly influence sports achievement at elementary school.